3a2 * 2a3

Question

Asked 8/7/2016 4:17:46 PM

Updated 8/7/2016 11:42:20 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

s

= a^4*3a^2 - a^4*2a + a^4

= 3a^6 - 2a^5 + a^4

jerry06|Points 64162|

= 8m - 4n + 6m + 3n;

= 14m - n

alfred123|Points 104663|

(-7)(8) + (-7)(k)

= -56 - 7k

Andrew.|Points 64158|

Question

Asked 8/7/2016 4:17:46 PM

Updated 8/7/2016 11:42:20 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Rating

3

3(m+n) = 3m + 3n

3(m+n)

= 3(m) + 3 (n)

= 3m + 3n

3(m+n)

= 3(m) + 3 (n)

= 3m + 3n

Added 8/7/2016 5:19:30 PM

This answer has been confirmed as correct and helpful.

Find the product mentally.
(2j + 7)(2j - 7) **Weegy:** (2j + 7)(2j - 7) = 4j^2 - 49 **User:** Find the product mentally.
(z - 12)(z + 12) **Weegy:** Find the product mentally. (z - 12)(z + 12)
z^2 - 144
**User:** Find the product mentally.
(2m - 9)2 **Weegy:** (2m - 9)^2 = (2m - 9)(2m - 9) = 4m^2 - 36m + 81 **User:** Select the correct product.
(a + 8)(b + 3) **User:** Find the product mentally.
[(x + 1)(x - 1)]2 (More)

Question

Not Answered

Updated 8/7/2016 11:34:30 PM

2 Answers/Comments

48j 5 k 2 ÷ (-3j 3 k)

Question

Not Answered

Updated 8/7/2016 10:57:53 PM

1 Answer/Comment

2x2 - 10x + 8 = 2(x - 1)(x - 4)

Added 8/7/2016 10:57:48 PM

This answer has been confirmed as correct and helpful.

Find the product mentally.
(ab + 3)(ab - 3) **Weegy:** (ab + 3)(ab - 3) = a^2b^2 - 3ab + 3ab - 9; = a^2b^2 - 9 (More)

Question

Updated 8/7/2016 11:32:22 PM

0 Answers/Comments

Simplify: 76 ÷ 72.

Question|Asked by kimmymunro2001

Updated 8/10/2016 9:54:59 PM

1 Answer/Comment

76 ÷ 72 = 19/18

Added 8/10/2016 9:54:59 PM

This answer has been confirmed as correct and helpful.

32,215,098

questions answered

There are no comments.